Implementasi Teori Pers Tanggung Jawab Sosial dalam Pemberitaan TVRI Pusat - Madrid De Fretes; Retor A.W. Kaligis (CoverAge: Journal of Strategic Communication, 2018)
The purpose of writing this research is to find out how the implementation of social responsibility press theory in the coverage of Central TVRI. In this study, the author only focuses on the forms of implementation of the theory of social responsibility press which are carried out in the news. Data collection techniques used are observation, interview and documentation. The theory used in this study is the Social Responsibility Theory of the Press, and the concepts used are mass media, television, and TVRI as public service partners. From the findings, it can be concluded that there are a number of indicators that are the main principles of social responsibility that TVRI has implemented, namely accepting and fulfilling obligations to the community, providing space for the community to convey a viewpoint as a form of community control to build a better TVRI, avoid reporting which can divide unity and unity, but TVRI has so far not been able to manage its institutions independently without any political intervention because the existing regulations limit the space for TVRI. In the news that hit the public and the government TVRI could not present information that was neutral because of government factors as a form of interpretation of the country so that TVRI took a position as a media that presented news that did not become a control of power.